2007
DOI: 10.1097/mnm.0b013e328013eaf7
|View full text |Cite
|
Sign up to set email alerts
|

The significance of FDG uptake in bilateral thyroid glands

Abstract: (1) Bilateral thyroidal uptake of FDG can be found in normal variants and subjects with various thyroid disorders, showing varieties of uptake patterns. (2) Diffuse intense uptake and higher SUV levels are a clue to a diagnosis of chronic thyroiditis, especially for those with hypothyroidism. (3) Focally intense uptake suggests the possibility of a thyroid carcinoma. (4) Sparse uptake associated with the thymus and symmetrical skeletal muscle uptake and lower SUV level raise the possibility of Graves' disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Accumulation of 18 F-FDG in normal thyroid tissue is usually low to absent because free fatty acids are preferred substrates for the thyroid gland (17). Diffuse thyroid uptake is generally regarded as benign and results from inflammatory etiologies, such as thyroiditis (18). Fibroblast infiltration also leads to continuous uptake of 18 F-FDG after treatment in patients with chronic thyroiditis (10).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accumulation of 18 F-FDG in normal thyroid tissue is usually low to absent because free fatty acids are preferred substrates for the thyroid gland (17). Diffuse thyroid uptake is generally regarded as benign and results from inflammatory etiologies, such as thyroiditis (18). Fibroblast infiltration also leads to continuous uptake of 18 F-FDG after treatment in patients with chronic thyroiditis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse thyroid uptake is generally regarded as benign and results from inflammatory etiologies, such as thyroiditis (18). Fibroblast infiltration also leads to continuous uptake of 18 F-FDG after treatment in patients with chronic thyroiditis (10). Tateishi et al (7) reported that diffuse thyroid uptake in patients with advanced breast cancer represents active inflammation caused by chronic thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations